Predictors of teacher-rated social problems in children with ADHD and children with LD. - Lim, Jing Han. (2011)
The present study investigates the incremental effects of attention problems, externalizing and internalizing problems and stressful life events in predicting teacher-rated social problems in children with ADHD, and separately, in children with LD. Multiple hierarchical regression models determined the unique contribution of each predictor with the order arranged accordingly to its theoretical importance to social impairment. Preliminary analysis indicated that children with ADHD did not suffer significantly more social problems than children with LD. For children with ADHD, externalizing and internalizing problems each contributed uniquely to social impairment. However, stressful life events was not a significant predictor. For children with LD, only internalizing problems and stressful life events contributed uniquely to social impairment, externalizing problems was not a significant predictor.